Lecturer–Learner Leadership and Its Impact on Student Learning Behavior in Islamic Higher Education - Nur Aedi; Richard Lionel Gorni (Jurnal Pendidikan Islam, 2025)
In today’s global higher education landscape, effective leadership is increasingly recognized as a pivotal factor in shaping student learning behaviour, particularly in Islamic educational institutions that balance academic and moral development. This study investigates the influence of lecturer–learner leadership on student learning behavior at Islamic Private Universities in Indonesia. Employing a quantitative research design, the study focused on two main variables: lecturer–learner leadership and student learning behavior. Data were collected from 21 Islamic Private Universities, involving 501 lecturers and 708 students, resulting in 1,209 valid questionnaire responses. The findings demonstrate that lecturer–learner leadership has a significant, positive effect on student learning behaviour. When lecturers embody strong leadership qualities in their interactions with students, such as guidance, support, and ethical modelling, students display more constructive, engaged, and independent learning behaviors. This emphasizes the crucial role of lecturer–learner dynamics in fostering both academic achievement and personal growth. The results highlight the importance of integrating learner-centered leadership values into the educational framework of Islamic universities. For Islamic higher education to meet global standards, institutions must empower lecturers with leadership competencies that cultivate active, ethical, and independent learners, thereby enhancing both educational quality and character formation.